Haematology and serum biochemistry of broilers fed grits from three cassava varieties as replacement for maize (2013)
An eight-week feeding trial was conducted to investigate the effect of 50% replacement of maize with grits prepared from three cassava varieties; TME 419, TMS 01/1371 and TMS 30572 as the major sources of energy oh the haematology and serum biochemistry of broilers. Four experimental diets were formulated in which cassava grits replaced maize at 0% for T I (control diet) and 50% of each treatments T2, T3 and T4 of TME 419, TMS 01/1371 and TMS 30572 cassava varieties, respectively. The replacements were same for Starter and finisher phases. One hundred and ninety-six day-old chicks of Abor acre strain were randomly allotted to four dietary treatments with seven replicates of seven birds per replicate in a completely randomized design. Haematology and serum biochemistry showed no significant differences (P > 0.05) at the end of the experiment. However, MCH, MCV and AST levels showed significant differences. Inclusion of grits made from whole roots of the three cassava varieties replaced 50% maize in broiler diets without detrimental effect on haematology and serum biochemistry.